Identification of Bacterial Composition in Freeze-Dried Agaricus bisporus During Storage and the Resultant Odor Deterioration - Yang, Wenjian; Wang, Liuqing; Hu, Qiuhui; Pei, Fei; Mugambi, Mariga Alfred (Frontiers in Microbiology, 2019)
Moisture absorption and bacterial growth are critical factors for the quality deterioration of freeze-dried Agaricus bisporus. In order to explore the bacterial composition and the resultant odor changes of freeze-dried A. bisporus during storage under three typical conditons (25 °C, 55% RH (RT); 37 °C, 85% RH (HT); ambient temperature (AT)), bacterial diversity and communities were analyzed using metagenomics, and volatile compounds was determined. The results demonstrated that the bacterial composition of freeze-dried A. bisporus was dominated by Pseudomonas, followed by Rhizobium and Pedobacter. In addition, Mucilaginibacter, Flavobacterium, and Thermus were a few other genera more dominant in HT samples, Chryseobacterium was the other genera more dominant in AT samples, while, Sphingobacterium and Chryseobacterium were a few other genera more dominant in RT samples. Furthermore, the increase of benzaldehyde content in HT samples may have been induced by the growth of Pseudomonads. Moreover, the esters production in RT and AT samples might have been induced by Chryseobacterium. This study provided comprehensive information on exogenous bacterial composition and the resultant odor in freeze-dried A. bisporus, which might be a theoretic fundament of quality control and quick quality monitor.